Gibberellin Promotes Sweetpotato Root Vascular Lignification and Reduces Storage-Root Formation - Singh, Vikram; Sergeeva, Lidiya; Ligterink, Wilco; Aloni, Roni; Zemach, Hanita; Doron-Faigenboim, Adi; Yang, Jun; Zhang, Peng; Shabtai, Sara; Firon, Nurit (Frontiers in Plant Science, 2019)
Sweetpotato yield depends on a change in the developmental fate of adventitious roots into storage-roots. The mechanisms underlying this developmental switch are still unclear. We examined the hypothesis claiming that regulation of root lignification determines storage-root formation. We show that application of the plant hormone gibberellin increased stem elongation and root gibberellin levels, while having inhibitory effects on root system parameters, decreasing lateral root number and length, and significantly reducing storage-root number and diameter. Furthermore, gibberellin enhanced root xylem development, caused increased lignin deposition, and, at the same time, decreased root starch accumulation. In accordance with these developmental effects, gibberellin application upregulated expression levels of sweetpotato orthologues of Arabidopsis vascular development regulators (IbNA075, IbVND7, and IbSND2) and of lignin biosynthesis genes (IbPAL, IbC4H, Ib4CL, IbCCoAOMT, and IbCAD), while downregulating starch biosynthesis genes (IbAGPase and IbGBSS) in the roots. Interestingly, gibberellin downregulated root expression levels of orthologues of the Arabidopsis BREVIPEDICELLUS transcription factor (IbKN2 and IbKN3), regulator of meristem maintenance. The results substantiate our hypothesis and mark gibberellin as an important player in regulation of sweetpotato root development, suggesting that increased fiber formation and lignification inhibit storage-root formation and yield. Taken together, our findings provide insight into the mechanisms underlying sweetpotato storage-root formation and provide a valuable database of genes for further research.